Visions of political violence - Ruggiero, Vincenzo (Routledge, 2020)
"This book offers a typology of different forms of political violence. From systemic and institutional violence, to the behaviour of crowds, to armed conflict and terrorism, Ruggiero draws on a range of perspectives from criminology, social theory, political science, critical legal studies and literary criticism to consider how these forms of violence are linked"--